2020
DOI: 10.1038/s41598-020-64671-4
|View full text |Cite
|
Sign up to set email alerts
|

Statistical learning of transition patterns in the songbird auditory forebrain

Abstract: visualized with an epifluorescence microscopy. Figure 1B shows the location of recording probes along with the two main structures of the auditory forebrain: field L2 and Caudomedial Nidopallium (NCM). Statistical Analyses. In the analysis using surprise index (SI), each sample is one site/unit and different statistical tests were used for comparisons based on MUA and SUA data. For MUA, we performed within-subject comparisons because comparisons are mostly within the same group of electrodes; for SUA, we perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…We did not test whether statistical learning for pain is automatic but, based on previous work, we expect it to happen spontaneously, without requiring the need to explicitly report stimulus probabilities. Indeed, statistical learning of visual or auditory inputs has been reported in songbirds, primates and newborns [28][29][30][31][32] . Furthermore, previous studies have shown implicit expectation effects from sequences of stimuli in humans [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…We did not test whether statistical learning for pain is automatic but, based on previous work, we expect it to happen spontaneously, without requiring the need to explicitly report stimulus probabilities. Indeed, statistical learning of visual or auditory inputs has been reported in songbirds, primates and newborns [28][29][30][31][32] . Furthermore, previous studies have shown implicit expectation effects from sequences of stimuli in humans [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted the importance of the caudomedial nidopallium (NCM), a higher order auditory processing area, in sensory learning in songbirds (12,13,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). For example, song learning leads to a subset of NCM neurons becoming selectively tuned to the tutor song (34), and manipulations of signaling cascades in NCM during developmental song learning affect tutor song imitation (35,36).…”
Section: Introductionmentioning
confidence: 99%